Phase II study of adjuvant docetaxel and carboplatin with/without doxorubicin and cyclophosphamide in triple negative breast cancer: a randomised controlled clinical trial - Najafi, Safa; Payandeh, Mehrdad; Sadeghi, Masoud; Shafaei, Vahideh; Shojaiyan, Fateme; Abbasvandi, Fereshte (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study: The aim of this trial was to compare overall survival (OS), disease-free survival (DFS), and toxicity of two adjuvant regimens in triple negative patients with Iranian ethnicity. Material and methods: In a phase II trial, patients with previously untreated triple negative breaststroke cancer were randomly assigned by using docetaxel 70 mg/m 2 and carboplatin AUC = 7 every three weeks with granulocyte colony-stimulating factor for sin courses (arm A) or doxorubicin hydrochloride 60 mg/m 2 and cyclophosphamide 600 mg/m 2 every three weeks with G-CSF for four courses followed by docetaxel 70 mg/m 2 and carboplatin AUC = 7 every three weeks with G-CSF for four courses (arm B). Results : A total of 119 patients were randomly enrolled in our study (60 patients in Arm A and 59 patients in Arm B) between 2011 and 2016. The mean follow-up was 40 months at the time of treatment analysis. The 2-year and 5-year DFS rates for Arm A were 92.7% vs. 85% and for Arm B were 82.6% vs. 64.4%. The 2-year and 5-year OS rates for Arm A were 96.5% vs. 91.7% and for Arm B were 90.5% vs. 81.3%. There was a significant correlation for DFS and OS in the two arms. There was no significant difference between adverse events with the two regimens. Conclusions : In our research, less progression was found with Arm A as compared to Arm B. Adding of anthracyclines such as doxorubicin hydrochloride did not increase OS and DFS in triple negative breast cancer (TNBC) patients.